Reduction of Pain and Blood Pressure in Hypertensive Elderly Through Combination Therapy of Progressive Muscle Relaxation and Religious Music Therapy - Susanty, Yunita Ery; Anwar, Syamsul; Badriah, Siti (Poltekita: Jurnal Ilmu Kesehatan, 2024)
A condition called hypertension affects the blood vessels when the patient's systolic and diastolic blood pressures are more than 140 and 90 mmHg, respectively. Pain scale and blood pressure in elderly hypertensive patients can be affected by religious music therapy and progressive muscle relaxation techniques that stretch muscles and increase calmness. The research design used was a quantitative pre-post quasi-experiment with a control group. This study involved 32 hypertensive elderly residents of Bengkulu Tresna Werdha Social Home as the population. Then the respondents were divided into two groups: 16 people in the intervention group and 16 people in the control group. For six consecutive days, the intervention group received a combination of progressive muscle relaxation and religious music therapy for 15 minutes every day. The findings showed that the cytolic, diastolic, and pain scales in elderly people with hypertension decreased after being given combined therapy with progressive muscle relaxation and religious music therapy (p value = 0.000). It is hoped that the results of this study can provide knowledge about complementary therapies that can be given to the elderly suffering from hypertension.